Langkah Menuju Industri Peternakan Sapi Bali di Nusa Tenggara Barat (NTB) Melalui Peternakan Terpadu Tanpa Limbah: Suatu Ulasan - Adji S Dradjat; U Abdullah (Caraka Tani: Journal of Sustainable Agriculture, 2006)
Three decades ago, West Nusa Tenggara or Nusa Tenggara Barat (NTB) was a resource of Bali cattle meat, to either provides national supply or export. However, since the year 2000, meat supply from NTB has been limited and there has been decreasing Bali cattle productivity. Low productivity of Bali cattle has been caused by severals factors such as: traditional way, in a small scale number cattle, in a relatively small size of land with limitation of feed availability in raising cattle. On the other hand, rice straw which potential for cattle feeding, has been burned which may induce pollution. In addition, cattle manure was also thrown to the field or to the river which may spread parasites infestation. As a consequuence, under NTB condition, Bali cattle has low productivity, with high cost of raising. Application of mixed farming may lead farm efficiency by reducing feeding cost, by using rice straws and processing manure as organic fertilizer. Mixed farming may provide solution to NTB farmers by leading zero waste and by inducing environmental friendly (eco-farming). Under mixed farming system, in order to improve cattle production, appropriate technology are essential to be implemented. Hopefully, production of Bali cattle and others agricultural comodities may increase optimally. Finally, higher income can be obtained and farmers may have a better live.